Technology of drinks based on water extracts of rosehip, sea buckthorn and viburnum - Капліна, Тетяна Вікторівна; Миронов, Денис Анатольевич (Eastern-European Journal of Enterprise Technologies, 2014)
The results of developing the technology of drinks, fruit drinks and fizzes, made of plant extracts of rosehip, sea buckthorn and viburnum, previously processed in the vortex layer of ferromagnetic particles are presented in the paper. Plant extracts were prepared by the traditional infusion at a constant temperature. Processing in the vortex layer of ferromagnetic particles allows to reduce the infusion time by 4-6 times in comparison with the industrial extraction technologies. Based on the studies, technologies of drinks “Shypshynka”, “Zhyvynka”, “Kalinka” fruit drinks “Syla”, “Badyorist”, “Energiya”, fizzes “Shypshynoviy”, “Oblipykhovyi”, “Kalynovyi” were developed. Previous studies have shown an increase in the content of biologically active substances in drinks, made using the developed technologies in comparison with traditional methods. In addition, the patterns of preserving high quality drinks, based on extracts from plant raw material, processed in the vortex layer of ferromagnetic particles were determined. A project of TU U “Soft drinks based on plant extracts” and technological instruction TI "Technological instruction for the production of soft drinks based on plant extracts" was developed.